(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Determing the molecular markers related to drug resistance in P. falciparum populations in four provinces of the Central Highlands. Research methods: Extracted total DNA was used for Nested-PCR techniques to identify four species of malaria parasites; PCR to capture the K13, Exonuclease, and Pfcrt genes; Sanger sequencing to sequence these gene fragments; and realtime-PCR to identify polymorphisms in the plasmepsin2 and Pfmdr1 genes. Results: The study revealed a high prevalence of the C580Y mutation in P. falciparum, which is associated with artemisinin resistance, along with the E415G mutation in the Exonuclease gene and polymorphisms in plasmepsin2 related to piperaquine resistance. Mutations in the Pfcrt gene, such as K76T and A220S (linked to chloroquine resistance), F145I (related to piperaquine resistance), and polymorphisms in the Pfmdr1 gene (associated with mefloquine resistance) were also identified. Conclusion: The study identified K13 mutations related to artemisinin resistance, the Exonuclease E415G mutation associated with piperaquine resistance, Pfcrt mutations linked to chloroquine resistance, as well as plasmepsin2 and Pfmdr1 polymorphisms related to piperaquine and mefloquine resistance.